New species of Nearctic oak gall wasps (Hymenoptera: Cynipidae, Cynipini) - Melika, George; Nicholls, James A.; Abrahamson, Warren G.; Buss, Eileen A.; Stone, Graham N. (Zootaxa, 2021)
Twenty nine new species of cynipid oak gall wasps from the Nearctic region (America north of Mexico) are described: Andricus archboldi Melika & Abrahamson, sp. nov., A. catalinensis Melika, Nicholls & Stone, sp. nov., A. chapmanii Melika & Abrahamson, sp. nov., A. chiricahuensis Melika, Nicholls & Stone, sp. nov., A. coconinoensis Melika, Nicholls & Stone, sp. nov., A. columbiensis Melika, Nicholls & Stone, sp. nov., A. cooki Melika, Nicholls & Stone, sp. nov., A. fitzpatricki Melika & Abrahamson, sp. nov., A. highlandensis Melika, Nicholls & Stone, sp. nov., A. mellificus Nicholls, Stone & Melika, sp. nov., A. menkei Melika & Abrahamson, sp. nov., A. mogollonensis Melika, Nicholls & Stone, sp. nov., A. nichollsi Melika & Stone, sp. nov., A. schickae Nicholls, Melika & Stone, sp. nov., A. torreyaensis Melika & Abrahamson, sp. nov., A. williami Melika, Nicholls & Stone, sp. nov., Antron lovellae Melika, Nicholls & Stone, sp. nov., A.tomkursari Melika, Nicholls & Stone, sp. nov., Dryocosmus archboldi Melika & Abrahamson, sp. nov., Loxaulus virginianae Melika & Buss, sp. nov., Neuroterus alexandrae Nicholls & Melika, sp. nov., N. aliceae Melika, Nicholls & Stone, sp. nov., N. bussae Melika & Nicholls, sp. nov., N. oblongifoliae Nicholls, Stone & Melika, sp. nov., N. quaili Melika, Nicholls & Stone, sp. nov., N. rosieae Melika, Nicholls & Stone, sp. nov., N. stonei Melika & Nicholls, sp. nov., Zapatella abrahamsoni Melika, sp. nov., Z. brooksvillei Melika & Abrahamson, sp. nov.. Alternate asexual and sexual generations are described for four species, Andricus archboldi Melika & Abrahamson, sp. nov., A. fitzpatricki Melika & Abrahamson, sp. nov., A. schickae Nicholls, Melika & Stone, sp. nov., Neuroterus aliceae Melika, Nicholls & Stone, sp. nov.. Descriptions, diagnoses, plus information on biology and host associations are given for all new species. All taxa are supported by morphological data; matching of generations is established using DNA sequence data. We also demonstrate that Neuroterus niger var. alimas Kinsey should be considered as a nomen dubium.